Soil carbon changes from conversion of forest to pasture in Brazilian Amazonia - Fearnside, Philip Martin; Barbosa, Reinaldo Imbrozio (Forest Ecology and Management, 1998)
Soils in Brazilian Amazonia may contain up to 136 Gt of carbon to a depth of 8 m, of which 47 Gt are in the top meter. The current rapid conversion of Amazonian forest to cattle pasture makes disturbance of this carbon stock potentially important to the global carbon balance and net greenhouse gas emissions. Information on the response of soil carbon pools to conversion to cattle pasture is conflicting. Some of the varied results that have been reported can be explained by effects of soil compaction, clay content and seasonal changes. Most studies have compared roughly simultaneous samples taken at nearby sites with different use histories (i.e., 'chronosequences'); a clear need exists for longitudinal studies in which soil carbon stocks and related parameters are monitored over time at fixed locations. Whether pasture soils are a net sink or a net source of carbon depends on their management, but an approximation of the fraction of pastures under 'typical' and 'ideal' management practices indicates that pasture soils in Brazilian Amazonia are a net carbon source, with the upper 8 m releasing an average of 12.0 t C/ha in land maintained as pasture in the equilibrium landscape that is established in the decades following deforestation. Considering the equilibrium landscape as a whole, which is dominated by pasture and secondary forest derived from pasture, the average net release of soil carbon is 8.5 t C/ha, or 11.7 x 106 t C for the 1.38 x 106 ha cleared in 1990. Only 3% of the calculated emission comes from below 1 m depth, but the ultimate contribution from deep layers may be substantially greater. The land area affected by soil C losses under pasture is not restricted to the portion of the region maintained under pasture in the equilibrium landscape, but also the portion under secondary forests derived from pasture. Pasture effects from deforestation in 1990 represent a net committed emission from soils of 9.2 x 106 t C, or 79% of the total release from soils from deforestation in that year. Soil emissions from Amazonian deforestation represent a quantity of carbon approximately 20% as large as Brazil's annual emission from fossil fuels.
Keywords: Deforestation; Global Carbon Budget; Land-use Change; Soil Carbon; Brazil, Amazonia